The Trends of Pharmacological Therapy in one Month Post Myocardial Infarction Patients: Pharmacological Therapy in Myocardial Infarction Patients - Liaquat Memon , Hussain; Ahmed Shaikh, Naveed; Naz, Mariam; Ahmed, Khalil; Rahman Khalid, Muhammad; ., Shahzad (Pakistan Journal of Health Sciences, 2023)
Guideline recommended treatment has an important impact on the mortality and morbidity of post myocardial infarction patients. Objective: To assess the frequency of appropriate drug with its appropriate dosage of guideline recommended pharmacological therapy, prescribed by physician, in patients with Myocardial Infarction (MI). The cross sectional study conducted at National Institute of Cardiovascular Disease, Karachi from 1st January 2020 to 30th June 2020. Methods: Total 160 patients who came to hospital for follow-up after one month of Myocardial infarction were included in the study. Prescription was considered appropriate if the patient has taken at-least 5 out of 6 medications. At least 5 out of 6 along with its goal dose was considered as appropriate dosage. Descriptive statistics were calculated. Stratification was done. Chi-square test was applied post stratification and p-value ≤ 0.05 was considered as significant. Results: There were 103 male and 57 female patients. The mean age was 53.36 ± 8.10 years. Number of drugs used was found appropriate in 96.3% patients but the doses of drugs used was found appropriate in only 5.6% patients. Conclusions: The present study revealed that the majority of the physicians prescribed the recommended number of the drugs used; however, the doses of drugs used were not always according to the guidelines. It is important for cardiology physicians to understand the importance of guideline recommended pharmacological intervention among patients with a one-month history of MI.